A study of the morphological variability in Cynara humilis L. and C. hystrix Ball (Asteraceae-Cardueae) - Wiklund, Annette (Lazaroa, 1989)
The two species Cynara humilis L. and C. hystrix Ball of the Asteraceae-Cardueae were found to intergrade in Morocco. A pictorialised dot map, showing the distribution of six characters in Moroccan herbarium specimens of the above species and intermediate morphs, was produced. The map revealed a pattern that suggests the occurrence of allopatric introgressive hybridisation.